Exhausting dance : performance and the politics of movement - Lepecki, André (New York ; London : Routledge, 2006)
The only scholarly book in English dedicated to recent European contemporary dance, 'Exhausting Dance: Performance and the Politics of Movement' examines the work of key contemporary choreographers who have transformed the dance scene since the early 1990s in Europe and the US. Through their vivid and explicit dialogue with performance art, visual arts and critical theory from the past thirty years, this new generation of choreographers challenge our understanding of dance by exhausting the concept of movement. Their work demands to be read as performed extensions of the radical politics implied in performance art, in post-structuralist and critical theory, in post-colonial theory, and in critical race studies. In this far-ranging and exceptional study, Andre Lepecki brilliantly analyzes the work of the choreographers: * Jerome Bel (France) * Juan Dominguez (Spain) * Trisha Brown (US) * La Ribot (Spain) * Xavier Le Roy (France-Germany) * Vera Mantero (Portugal) and visual and performance artists: * Bruce Nauman (US) * William Pope.L (US). This book offers a significant and radical revision of the way we think about dance, arguing for the necessity of a renewed engagement between dance studies and experimental artistic and philosophical practices.
Introduction : the political ontology of movement -- Masculinity, solipsism, choreography : Bruce Nauman, Juan Dominguez, Xavier Le Roy -- Choreography's "slower ontology" : Jérôme Bel's critique of representation -- Toppling dance : the making of space in Trisha Brown and La Ribot -- Stumbling dance : William Pope. L's crawls -- The melancholic dance of the post-colonial spectral : Vera Mantero summoning Josephine Baker -- Conclusion : exhausting dance : to be done with the vanishing point.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Bel, Jérôme; Dominguez, Juan; Brown, Trisha; La Ribot; Le Roy, Xavier; Mantero, Vera; Nauman, Bruce; Pope, William L